2006
DOI: 10.1016/s1472-6483(10)61082-6
|View full text |Cite
|
Sign up to set email alerts
|

Medical treatment to improve sperm quality

Abstract: Approximately 30% of cases of couple infertility are due to a male factor. Several conditions can interfere with spermatogenesis and reduce sperm quality and production. Treatable conditions, such as hypogonadism, varicocele, infections and obstructions, should be diagnosed and corrected, but many aspects of male factor infertility remain unclear. Various agents have been used in the attempt to increase the fertility potential of subjects with idiopathic oligoteratoasthenozoospermia. The rationale of medical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 101 publications
0
56
1
1
Order By: Relevance
“…Hesperidin also showed the ability to penetrate the blood-brain barrier in an in vitro model. Infertility is one of the major health problems in life, and approximately 30% of infertilities are due to a male factor (Isidori et al, 2006;Carlsen et al, 1992). Several conditions can interfere with spermatogenesis and reduce sperm quality and production.…”
Section: Introductionmentioning
confidence: 99%
“…Hesperidin also showed the ability to penetrate the blood-brain barrier in an in vitro model. Infertility is one of the major health problems in life, and approximately 30% of infertilities are due to a male factor (Isidori et al, 2006;Carlsen et al, 1992). Several conditions can interfere with spermatogenesis and reduce sperm quality and production.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, sperm centrifugation was selected as a method for ISA depending of the results of the Shaaban (2007) [25]. With respect to sperm functional capacity, each laboratory should determine the centrifugation force and centrifugation time that are necessary to form a manageable recovery of sperm [26]. SMART-Pro medium which invented by Fakhrildin and Flayyih (2011) [27], medium was prepared based on Ringer solution supplemented with two essential additives Sodium lactate and/or pyruvate and human serum albumin (HSA) (5% or 10%).…”
Section: Discussionmentioning
confidence: 99%
“…Varicoceles palpable in a patient lying on his back are suspected to be symptomatic ones and thus must be further investigated by ultrasound or other imaging techniques. In some studies, an improved seminal fluid and/or increased testicular volume have been observed after varicocelectomy [17,18]. The prevalence of other benign alterations in testes is much lower.…”
Section: Palpation Of the Testes And Its Acceptance S H O R T C O M Mmentioning
confidence: 99%